Czynniki decydujące o wyborze miejsca zakupu żywności (na przykładzie województwa podkarpackiego) - Cyran, Kazimierz; Wierzbiński, Bogdan (Factors Deciding of the Food Shopping Place (on the Example of Podkarpacki Voivodship), 2005)
Arising competition causes that a firm which wants to achive more competitiveness, especially on the field of costumer behaviour, must know the costumer decision making.Among factors which are imporatant in the range of food buyer decision making process, the really important meaning has a place when buyers want to buy food products. But the most important meaning in the costumer behaviour has the lower price, convienient place of a shop and assortment of shops. The method of selling used by food shops is also important. The vast majority of consumers prefers to do shopping in medium sized, self-service shops.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 1, s. 102-108